Analysis of the current state of the manifestations of crime with evidence of corruption in prisons in Ukraine - Бондарчук, Олег Григорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
This article analyzes the current state of corruption in prisons in Ukraine. In view of the study indicated the reasons for its occurrence and the imperfection of the methods to identify the signs of corruption offenses.